2018
DOI: 10.1021/acsomega.8b01948
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graphene Oxide on Algal Organic Matter of Microcystis aeruginosa

Abstract: Graphene oxide (GO) as a novel and promising material has a huge market and multiple applications. The release of GO into the aquatic system during their life cycle would lead to potential risks for the environment and aquatic organisms. This study evaluated the impacts of GO on algal growth and algal organic matter (AOM) of Microcystis aeruginosa. GO exhibited moderate effects on algal growth and the photosynthetic system. There was no evident influence on cell density and chlorophyll-a content at GO concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Despite the large consensus on these effects, they were not always confirmed even when similar GO concentrations were applied. 138,139 These differences could be due to different exposure modalities or physiological characteristics of the target organisms. Because of the latter factor, effects may vary.…”
Section: Impact On Cyanobacteria and Algaementioning
confidence: 99%
See 1 more Smart Citation
“…Despite the large consensus on these effects, they were not always confirmed even when similar GO concentrations were applied. 138,139 These differences could be due to different exposure modalities or physiological characteristics of the target organisms. Because of the latter factor, effects may vary.…”
Section: Impact On Cyanobacteria and Algaementioning
confidence: 99%
“…The effects include induction of oxidative stress due to internalization of the flakes into the cell, physical damage to cell membranes due to the extreme hardness and low thickness of flakes, , and shading due to agglomeration of 2D nanomaterial particles with the cells, , although agglomeration is not a toxicity mechanism. Despite the large consensus on these effects, they were not always confirmed even when similar GO concentrations were applied. , These differences could be due to different exposure modalities or physiological characteristics of the target organisms. Because of the latter factor, effects may vary.…”
Section: Impact On Cyanobacteria and Algaementioning
confidence: 99%
“…369 GO does not inflict damage to the Microcystis aeruginosa, but it has a strong adsorption capacity that contributes to the removal of extracellular organic matter, such as humic acid-and fulvic acid-like organics. 370 In zebrafish embryos, GO inhibited cell growth, induced hatching delay and cardiac edema, and caused damage to chorion protuberances. 371 Limited research on BP's aquatic toxicity has been reported.…”
Section: Aquatic Toxicity Of Bpmentioning
confidence: 99%
“…Chemically exfoliated WS 2 nanosheets cause oxidative stress, lipid peroxidation, and membrane damage and alter metabolites and metabolic pathways in Chlorella vulgaris . GO does not inflict damage to the Microcystis aeruginosa , but it has a strong adsorption capacity that contributes to the removal of extracellular organic matter, such as humic acid- and fulvic acid-like organics . In zebrafish embryos, GO inhibited cell growth, induced hatching delay and cardiac edema, and caused damage to chorion protuberances .…”
Section: Ecosystem Risksmentioning
confidence: 99%
“…It is interesting to note that the maximum peaks associated with chlorophyll (a) in the visible region (600-700 nm) were clearly observed for a high concentration of GO mixed with the alga (2 GO-Al). It is important to report that GO is more hydrophilic than graphene and CNT due to the high level of oxygen-containing functional groups on the basal plane and is reported not to inflict damage on alga [27]. GO bears negative surface charges containing hydroxyl and epoxide functional groups and has a colloidal stability in biological media [28,29].…”
Section: Optical Propertiesmentioning
confidence: 99%